Real-time observation of X-ray-induced intramolecular and interatomic electronic decay in CH2I2 - Hironobu Fukuzawa; Tsukasa Takanashi; Edwin Kukk; Koji Motomura; Shin-ichi Wada; Kiyonobu Nagaya; Yuta Ito; Toshiyuki Nishiyama; Christophe Nicolas; Yoshiaki Kumagai; Denys Iablonskyi; Subhendu Mondal; et al. (NATURE PUBLISHING GROUP, 2022)
The increasing availability of X-ray free-electron lasers (XFELs) has catalyzed the development of single-object structural determination and of structural dynamics tracking in realtime. Disentangling the molecular-level reactions triggered by the interaction with an XFEL pulse is a fundamental step towards developing such applications. Here we report real-time observations of XFEL-induced electronic decay via short-lived transient electronic states in the diiodomethane molecule, using a femtosecond near-infrared probe laser. We determine the lifetimes of the transient states populated during the XFEL-induced Auger cascades and find that multiply charged iodine ions are issued from short-lived (similar to 20 fs) transient states, whereas the singly charged ones originate from significantly longer-lived states (similar to 100 fs). We identify the mechanisms behind these different time scales: contrary to the short-lived transient states which relax by molecular Auger decay, the long-lived ones decay by an interatomic Coulombic decay between two iodine atoms, during the molecular fragmentation.